Managing Postpartum Hemorrhage in Remote and Border Areas: A Qualitative Study of Midwives' Experiences - Yolanda Montessori; Silvia Finida Hannisa; Paskalia Tri Kurniati; Yunida Haryanti; Lea Masan; Rizki Amartani (Gayaku Publisher, 2026)
Background: Postpartum hemorrhage remains one of the leading causes of maternal mortality worldwide, particularly in low- and middle-income countries. Midwives working in remote and border areas play a critical role in managing obstetric emergencies; however, they frequently encounter limited resources, restricted access to healthcare facilities, and geographical barriers that affect the quality of maternal healthcare services. Objective: This study aimed to explore midwives' experiences in managing postpartum hemorrhage emergencies in remote and border areas of Sintang Regency, West Kalimantan. Methods: This study employed a qualitative research design with a phenomenological approach. Seven midwives were selected using the snowball sampling technique. Data were collected through semi-structured interviews and analyzed using Braun and Clarke's thematic analysis. The trustworthiness of the data was ensured through the criteria of credibility, transferability, dependability, and confirmability based on the Lincoln and Guba framework. Results: The findings identified five major themes: (1) early recognition of postpartum hemorrhage; (2) emergency management of postpartum hemorrhage; (3) challenges in providing care in remote and border areas; (4) clinical decision-making and professional responsibility; and (5) midwives' adaptation and resilience. The results indicate that successful management of postpartum hemorrhage depends not only on midwives' clinical competence but also on their ability to make rapid clinical decisions, adapt to limited resources, and effectively coordinate referral systems. Conclusion: Effective management of postpartum hemorrhage emergencies in remote and border areas requires a combination of clinical competence, sound clinical decision-making, adaptive capacity, and responsive referral systems. Strengthening midwives' capacity and ensuring equitable distribution of healthcare resources are essential to improving the quality of emergency obstetric care and reducing maternal mortality in underserved areas. Suggestion: Governments and healthcare providers are encouraged to strengthen continuous professional training for midwives, improve obstetric referral systems, and ensure equitable access to healthcare personnel, essential medical equipment, medications, and supporting facilities in remote and border areas. Future studies are recommended to explore the perspectives of other key stakeholders and evaluate the effectiveness of interventions aimed at strengthening emergency obstetric care in resource-limited settings.